Peran Bimbingan Orang Tua dalam Pengembangan Kreativitas Anak di Kelurahan Galung Maloang Kota Parepare - Sulkifli (Indonesian Journal of Islamic Counseling, 2023)
Children generally need help from parents to develop themselves, including creativity, which is rarely the focus of parents. This research aims to determine the level of children's creativity, the barriers or constraints experienced by parents in guiding them, as well as the role played by parents as guides in increasing children's creativity in Galung Maloang Village, Parepare City. This research uses qualitative research through observation, interviews and observations. The research results showed that of the five children whose creativity was guided by their parents, on average the children had high curiosity, although there were also children who had low curiosity. Some children have a desire to explore new experiences, high self-confidence, and high imagination. The results of further research show that the obstacles experienced by parents in developing children's creativity are parents' lack of understanding about what creativity is and how to develop children's creativity, then parents' work which sometimes reduces interaction and guiding activities, and lack of support from partners. . Other research results show that there are several important roles for parents in developing children's creativity. First there is the role of care, then the role of education and the role of facilitator